2019
DOI: 10.1016/j.ebiom.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate diagnostic and prognostic biomarkers for pancreatic carcinoma

Abstract: BackgroundPancreatic carcinoma (PC) is one of the most aggressive cancers affecting human health. It is essential to identify candidate biomarkers for the diagnosis and prognosis of PC. The present study aimed to investigate the diagnosis and prognosis biomarkers of PC.MethodsDifferentially expressed genes (DEGs) were identified from the mRNA expression profiles of GSE62452, GSE28735 and GSE16515. Functional analysis and the protein-protein interaction network analysis was performed to explore the biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 50 publications
3
95
0
Order By: Relevance
“…Not surprisingly, we found that some of these genes were reported and associated with cancer. In HCC-unfavorable gene set, STEAP1B, TMC7, CYP19A1 and PNCK associated with prostate cancer, pancreatic carcinoma, breast cancer, respectively [16][17][18][19]. Here, we found them may also be associated with HCC.…”
Section: Discussionmentioning
confidence: 65%
“…Not surprisingly, we found that some of these genes were reported and associated with cancer. In HCC-unfavorable gene set, STEAP1B, TMC7, CYP19A1 and PNCK associated with prostate cancer, pancreatic carcinoma, breast cancer, respectively [16][17][18][19]. Here, we found them may also be associated with HCC.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly CENPF and SERBINB5 were also included in this panel of prognostic genes. Both of these genes were also identified in our panel [51]. SLC6A14 has been investigated as a potential novel therapeutic target for pancreatic cancer using α-methyltryptophan as a pharmacological inhibitor of SLC6A14 and showed reduced proliferation and clonogenic survival [52].…”
Section: Discussionmentioning
confidence: 74%
“…After referring to previously published literature, we selected four prognostic risk models, including 15gene signature (Chen) [21], 7-gene signature (Cheng) [22], 5-gene signature (Raman) [23], and 9-gene signature (Wu) [24] for the comparison with our 9-genes model. To ensure comparability, we calculated the risk score of each PAAD sample in the TCGA using the same method based on the corresponding genes in the 4 models, and evaluated the ROC of each model, and divided the samples into Risk-H and Risk-L groups in accordance with the median risk score.…”
Section: Comparison Of Risk Model With Other Modelsmentioning
confidence: 99%
“…Chen et al constructed a 15-gene signature to predict the prognosis of patients with early pancreatic ductal cancer [21]. Cheng et al constructed a 7-gene signature for the prognosis of pancreatic cancer based on multiple GEO cohorts [22]. In addition, the 5-gene signature was constructed by by Raman et al…”
Section: Clinical Validation Of 9 Genesmentioning
confidence: 99%